How to endure presentism. Issue 6 (3rd July 2019) - Baron, Sam
ABSTRACT: Presentism and endurantism are natural bedfellows: arguments have been mounted from endurantism to presentism and vice versa. I generalise an argument against the compatibility between presentism and endurantism offered recently by Tallant (forthcoming. "Presentism, Persistence and Trans-temporal Dependence." Philosophical Studies ). I then show how to reformulate endurantism so that it is compatible with presentism. I demonstrate that this reformulated version of endurantism can do the same work with respect to the problem of temporary intrinsics as can standard definitions.